Optical Properties of Dy3+ Doped Boro-tellurite Glasses - Tuyen, Vu Phi (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: Dy 3+ -doped glasses with various compositions (30+ x )B 2 O 3 + (60- x )TeO 2 + 9Na 2 O + 1Dy 2 O 3 ( x = 10 and 20) were prepared by a melt–quenching technique. The specifically structural properties of boro-tellurite glasses with the high borate content (> 30 mol%) was reflected in the unusually large values of the Judd-Ofelt parameters Ω 2 and Ω 6 . The CIE chromaticity color coordinates were calculated from the luminescence spectra of Dy 3+ ions of the glasses with the different compositions and all of them were located in the white light zone of the color coordination diagram. Keywords: Boro-tellurite, Dy 3+ , white light.